2011
DOI: 10.1589/jpts.23.237
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Manual Resistance Training on Improving Muscle Strength of the Lower Extremities of the Community Dwelling Elderly -A Clinical Intervention Study with A Control Group-

Abstract: Abstract. [Purpose] This study focused on the effects of Manual Resistance Training (MRT) performed by elderly people for their lower extremities. [Subjects and Methods] The subjects were 53 elderly persons. The isometric strength of the right knee-extensor of the subjects in the intervention group was assessed after MRT once a week for 12 weeks followed by MRT, twice a week for 12 more weeks. Subjects in the control group only received the muscle strength measurement and did not perform MRT.[Results] From th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
4
0
3
Order By: Relevance
“…Finally, because the experimental group only consisted of males and females in their 20s, the results cannot be generalized to all ages. The present results along with those of studies assessing resistance exercise for the elderly 26 ) , aerobic exercise 27 ) , aquatic exercise 28 ) , treadmill walking 29 ) , and muscular exhaustion recovery 30 ) are expanding the knowledge of the relationships of muscle groups with RPE.…”
Section: Discussionmentioning
confidence: 70%
“…Finally, because the experimental group only consisted of males and females in their 20s, the results cannot be generalized to all ages. The present results along with those of studies assessing resistance exercise for the elderly 26 ) , aerobic exercise 27 ) , aquatic exercise 28 ) , treadmill walking 29 ) , and muscular exhaustion recovery 30 ) are expanding the knowledge of the relationships of muscle groups with RPE.…”
Section: Discussionmentioning
confidence: 70%
“…However, considering that only a small portion of the world population attend gyms 5 , recent studies have suggested alternative forms that do not depend on equipment in order to permit the application of RT in nonspecific environments and places such as residential condominiums, hospitals, clinics, basic health units, universities, schools, and companies, among others [6][7][8][9] . One alternative of RT that is being investigated is manual resistance training (MRT) [7][8][9][10] , a concept that uses manual resistance imposed by a second person in the direction opposite to the movement performed by the exercising subject ( Figure 1A, 1B). Previous studies have shown that MRT is effective in increasing strength levels in different populations [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…One alternative of RT that is being investigated is manual resistance training (MRT) [7][8][9][10] , a concept that uses manual resistance imposed by a second person in the direction opposite to the movement performed by the exercising subject ( Figure 1A, 1B). Previous studies have shown that MRT is effective in increasing strength levels in different populations [7][8][9][10] . Furthermore, the effects of MRT are similar to those of free weight resistance training (FWRT) as long as the volume and intensity are comparable 7,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em âmbito clínico e em populações especiais, estudos mostraram que o TRM foi superior ao controle em promover melhora sobre a força e capacidade funcional de adolescentes [11] e idosos institucionalizados [12].…”
Section: Introductionunclassified